Introduction to astrobiology - Gilmour, Iain; Sephton, Mark A (Cambridge, Cambridge University Press, 2002)
Compiled by a team of experts, this textbook has been designed for elementary university courses in astrobiology. It begins with an examination of how life may have arisen on Earth and then reviews the evidence for possible life on Mars, Europa and Titan. The potential for life in exoplanetary systems and the search for extraterrestrial intelligence are also discussed. The text contains numerous useful learning features such as boxed summaries, student exercises with full solutions, and a glossary of terms. It is also supported by a website hosting further teaching materials. Written in an accessible style that avoids complex mathematics, this book is suitable for self-study and will appeal to amateur enthusiasts as well as undergraduate students. It contains numerous helpful learning features such as boxed summaries, student exercises with full solutions, and a glossary of terms. The book is also supported by a webstite hosting further teaching materials.
Appendix A-C, 330-339p.; Glossary 340-346p.; Index 351-358p.